Interactive robotic platform for education and language skill rehabilitation - Ishak, Nor Izzati; Md Yusof, Hazlina; Sidek, Shahrul Naim; Jaalan, Zaleha (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, we present the mechanism and system design of a robot that is suitable for rehabilitation process for autistic children. Through some researches, robot seems to have the ability to improve the communication skills of the children with autism. An interactive robotic platform has been developed taking into consideration the robot appearance and features to encourage positive outcome in the rehabilitation of autism spectrum disorder (ASD) children. The interaction between the robot and the child included language skills, eye contact, imitation behavior, facial expression and movement of the robot. Here, a high-level controller is integrated to the system to help therapist monitors the children’s reactions towards the robot. In result, the developed robot has the ability to help therapist to diagnose and conclude the therapy session in a shorter period.